Tourism Suitability Analysis of Dreamland Beach as Recreational Object - Augustine, Felicia; Watiniasih, Ni Luh; Ernawati, Ni Made (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
The research was conducted in Dreamland beach, Pecatu Village, Bali. The purpose of this research is to identify the potential and the tourism suitability index of Dreamland beach. The research was carried out from the start of January to the end of February 2021. The method used for this research is the descriptive quantitative method. Furthermore, the researcher uses the purposive sampling method to group the location into three location points. There are three points measured in the tourism suitability index, including depth, type of beach, the width of the beach, the base material of the water, slope of the beach, current velocity, brightness, beach land cover, dangerous species, and availability of freshwater. The research shows Dreamland has various potentials such as white sand, big waves, and moderate sloping cliff which enables visitors to enjoy the sunset. As a tourist destination, Dreamland is equipped with several facilities including restaurants, toilets, and kiosks. Moreover, visitors can rent umbrellas and surfing boards. Additionally, for safety purposes, there will be a lifeguard on duty. Access to Dreamland is easy, it has two parking spots. Parking spot 1 is designated for motorcycles, whereas parking spot 2 is designated for cars and buses. Based on this research, Dreamland achieved a good Tourism suitability index at 2.51 at locations 1 and 2.59 at locations 2 and 3. The parameters which act as the limiting factors are the current velocity and brightness. High-velocity current results in the mixture of sedimentation and seawater which leads to murky water, thus low visibility rate.